Teachers’ Perceptions on The Implementation of Merdeka Curriculum in English Learning - Masitoh, Imas; Gumelar, Rizdki Elang; Novari , Ari Fajria (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2024)
This research paper aims to determine Teachers' Perceptions on the Implementation of Merdeka Curriculum In English Learning at Phase E of Madrasah Aliyah Mathla'ul Anwar Pusat Menes Pandeglang – Banten In Academic Year 2023/2024. This research paper uses a qualitative approach with a content analysis design. The data collection method used was triangulation, namely observation, interviews and documentation. Data obtained from observation. Interviews were conducted with the principal, deputy principal for curriculum and English teachers. Documentation is carried out by immortalizing the interview process activities. Data analysis was carried out to analyze important findings as expected by the research objectives. Research findings show that the implementation of the Merdeka Curriculum received a positive perception. Apart from that, the structure of the Merdeka Curriculum is different from the previous curriculum. Based on the findings of this research, the Merdeka Curriculum received a positive perception because it focused on increasing student creativity. These findings also hope that other researchers will analyze or maximize research on implementing the Merdeka Curriculum in English language learning.